Perbedaan Hasil Belajar Peserta Didik Menggunakan Media Powerpoint dan Media Gambar pada Mata Pelajaran IPAS Kelas IV SD Negeri Samata Kab. Gowa - Ahmad, Nurzakiya; Ismail, . Ilyas; Munirah, Munirah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the differences in students’ learning outcomes in the IPAS subject taught using PowerPoint media and image media in Grade IV of SD Negeri Samata, Gowa Regency. The study employed a quasi-experimental method with a non-equivalent control group pretest-posttest design. The research population consisted of all 73 fourth-grade students, with a sample of 48 students selected using purposive sampling. Data were collected using learning outcome tests and documentation, then analyzed descriptively. The average learning outcome of students taught using PowerPoint media was 76.13, which falls into the “good” category, while the average score of students taught using image media was 74.38, also categorized as “good.” The results of the analysis using the non-parametric Mann-Whitney U test showed an Asymp. Sig. (2-tailed) value of 0.66 > 0.05, indicating that there was no significant difference between the two groups. Based on these findings, it can be concluded that both PowerPoint media and image media are equally effective in supporting students’ learning outcomes in the IPAS subject for Grade IV.